Selective vitamins as potential options for dietary therapeutic interventions: In silico and In vitro insights from mutant C terminal fragment of FGA - Pande M.; Kundu D.; Srivastava R. (My University, 2025)
We have used an integrated computational approach to explore the role of vitamin C and vitamin D in preventing aggregation of Fibrinogen A alpha-chain (FGActer) protein responsible for renal amyloidosis. We modelled structures of E524K / E526K mutants of FGActer protein and examined the potential interactions of these mutants with vitamin C and vitamin D3. Interaction of these vitamins at the amyloidogenic site may prevent the intermolecular interaction required for amyloid formation. The binding free energy values of vitamin C and vitamin D3 for E524K FGActer and E526K FGActer are − 67.12 ± 30.46 kJ/mole and − 79.45 ± 26.12 kJ/mol, respectively. Experimental studies using Congo red absorption, aggregation index studies and AFM imaging show encouraging results. The AFM images of E526K FGActer contained more extensive and higher protofibril aggregates, whereas, in the presence of vitamin D3, small monomeric and oligomeric aggregates were observed. Overall, the works provide interesting results about vitamin C and D role in preventing renal amyloidosis. © 2023 Elsevier Ltd